2021
DOI: 10.1098/rsob.210009
|View full text |Cite
|
Sign up to set email alerts
|

Fic and non-Fic AMPylases: protein AMPylation in metazoans

Abstract: Protein AMPylation refers to the covalent attachment of an AMP moiety to the amino acid side chains of target proteins using ATP as nucleotide donor. This process is catalysed by dedicated AMP transferases, called AMPylases. Since this initial discovery, several research groups have identified AMPylation as a critical post-translational modification relevant to normal and pathological cell signalling in both bacteria and metazoans. Bacterial AMPylases are abundant enzymes that either regulate the function of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 120 publications
0
3
0
Order By: Relevance
“…Recently we have reported that the yeast IMS-localized Fmp40 protein, belonging to the highly evolutionarily conserved SelO family, is regulated by its oxidation and reduction 10 . SelO proteins have an AMPylase activity, in which the adenosine monophosphate (AMP) moiety is attached to the threonine, serine, or tyrosine residues in proteins, and are active when they are in a reduced state 11,12 . Fmp40 is the only identified AMPylase in Saccharomyces cerevisiae to date.…”
Section: Introductionmentioning
confidence: 99%
“…Recently we have reported that the yeast IMS-localized Fmp40 protein, belonging to the highly evolutionarily conserved SelO family, is regulated by its oxidation and reduction 10 . SelO proteins have an AMPylase activity, in which the adenosine monophosphate (AMP) moiety is attached to the threonine, serine, or tyrosine residues in proteins, and are active when they are in a reduced state 11,12 . Fmp40 is the only identified AMPylase in Saccharomyces cerevisiae to date.…”
Section: Introductionmentioning
confidence: 99%
“…The human AMPylase, FICD, and its C. elegans ortholog, FIC-1, belong to a family of fic domain-containing AMPylases present as a single copy in metazoans ( Truttmann and Ploegh, 2017 ; Casey and Orth, 2018 ; Chatterjee and Truttmann, 2021 ). Fic AMPylases are bi-functional, catalyzing both the addition (AMPylation) and the removal (deAMPylation) of an adenosine monophosphate (AMP) moiety to serine or threonine hydroxyl groups of target proteins using a single active site ( Ham et al, 2014 ; Preissler et al, 2015 , 2017a , b ; Sanyal et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…FICD AMPylates and deAMPylates the ER-resident HSP70 family chaperone BiP on Thr518 and Thr356, which serves as a mechanism to regulate client binding and refolding activity of the cellular BiP pool ( Truttmann and Ploegh, 2017 ; Casey and Orth, 2018 ; Chatterjee and Truttmann, 2021 ). Similarly, FIC-1 AMPylates the two presumable functionally redundant C. elegans BiP orthologs HSP-3 and HSP-4 in the ER.…”
Section: Introductionmentioning
confidence: 99%